Non-identifier-based adaptive control of continuous fluidized bed spray granulation. (November 2018) - Palis, Stefan
Highlights: Non-identifier-based adaptive control is investigated as an alternative approach to model-based control. Application requirements are checked directly for the population balance model, i.e. the distributed parameter system. Two schemes, universal adaptive and lambda-tracking, are investigated. Abstract: This paper is concerned with stabilizing control for continuously operated fluidized bed spray granulation with internal product classification. It is well-known that these processes may become unstable for certain operating conditions giving rise to nonlinear oscillations in the particle size distribution. In contrast to previous works, in this contribution a model-free adaptive control is proposed. It is shown that the given fluidized bed spray granulation process fulfills the required structural assumptions. The designed control schemes, universal adaptive and λ -tracking control, are tested in a noise-free scenario and including measurement noise.